Nevogenesis Mechanisms and Clinical Implications of Nevus Development - Marghoob, Ashfaq A.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
Paul Gerson Unna$1 (Bs (3z(BAbtropfung(3y (Btheory that nevi develop through migration of nevus cells from the epidermis to the dermis prevailed for almost a century until the (3z(BHochsteigerung(3y (Btheory postulated the reverse pattern of migration based on newly acquired observations from histopathology and studies of embryogenesis. Most recently, however, new insights gained from epidemiology, cross-sectional and longitudinal studies of nevi, dermoscopy and confocal microscopy, and cellular and molecular studies have brought into question both of the aforementioned theories. This book provides a comprehensive guide to current knowledge about nevogenesis by presenting these latest advances and in addition discusses issues yet to be resolved. It will assist practicing physicians in effectively managing patients with a variety of nevi and will also be of great value to researchers in the field. Importantly, since nevi are associated with an increased risk of melanoma, understanding nevogenesis may help to unravel some of the mysteries of melanomagenesis.s
Nevogenesis: Changing Theories -- Classifying Melanocytic Nevi -- Evolution of Nevi -- The Dual Pathway of Nevogenesis -- Confocal Microscopy: Improving Our Understanding of Nevogenesis -- Nevi In Children And Adults: Dermoscopic Patterns And The Development of New Nevi -- Etiology of Congenital Melanocytic Nevi And Related Conditions -- Molecular Nevogenesis -- Nevogenesis: A Benign Metastatic Process? -- Nevus Senescence -- Gene-Environment Interactions In Nevogenesis -- Malignant Transformation of Melanocytic Nevi -- Disappearance of Melanocytic Nevi.
Keywords: Medicine; Dermatology; Oncology; Medicine & Public Health; Dermatology; Oncology